An Analysis of Students Dropout in Sociology at Dhawalagiri Multiple Campus, Baglung - Panta, Saroj Raj (Dhaulagiri Journal of Contemporary Issues, 2023)
The main aim of this paper is to investigate the factors influencing the dropout rate at Dhawalagiri Multiple Campus. Similarly, it aims to explore the reasons behind students' dropouts. A survey research design was used to describe the dropout rate. 26 respondents were selected through purposive sampling. Telephone, Messenger, Viber, and WhatsApp interviews were also used for collecting the required information. Assistant campus chiefs, department heads, and the chairperson of the Free Student Union's views were interviewed. This study is based on factors associated with dropout, such as age, gender, marital status, position in the number of siblings, health problems, family environment, fulfilled expectations, family and personal obligations, motivation in relation to the teaching and learning process, self-regulation, and time management. Beside these, family, community, college, and national education policies This study found that there are student-related indicators, campus-related indicators, family-related indicators, and socio-economic and cultural-related indicators. There are several reasons for dropping out of DMC. The main reasons for dropout, as explored by family-related indicators, were a lack of financial support from home and different family problems. The student-related indicators were their low academic achievement in examinations, irregularity in class, and willingness to go abroad; the campus-related indicators were a lack of academic support, feedback, motivation, and encouragement from teachers, a delay in exam results, and problems with institutional information systems. The implication of this study is to solve the problem of dropouts in the development of higher education programs in Nepal. This article will be helpful for academia, researchers, and planners.